BHBA Suppresses LPS-Induced Inflammation in BV-2 Cells by Inhibiting NF-κB Activation. (6th April 2014) - Fu, Shou-Peng; Li, Su-Nan; Wang, Jian-Fa; Li, Yang; Xie, Shan-Shan; Xue, Wen-Jing; Liu, Hong-Mei; Huang, Bing-Xu; Lv, Qing-Kang; Lei, Lian-Cheng; Liu, Guo-Wen; Wang, Wei; et al.
Abstract : β -Hydroxybutyric acid (BHBA) has neuroprotective effects, but the underlying molecular mechanisms are unclear. Microglial activation plays an important role in neurodegenerative diseases by producing several proinflammatory enzymes and proinflammatory cytokines. The current study investigates the potential mechanisms whereby BHBA affects the expression of potentially proinflammatory proteins by cultured murine microglial BV-2 cells stimulated with lipopolysaccharide (LPS). The results showed that BHBA significantly reduced LPS-induced protein and mRNA expression levels of iNOS, COX-2, TNF- α, IL-1 β, and IL-6. Blocking of GPR109A by PTX resulted in a loss of this anti-inflammatory effect in BV-2 cells. Western blot analysis showed that BHBA reduced LPS-induced degradation of I κ B- α and translocation of NF- κ B, while no effect was observed on MAPKs phosphorylation. All results imply that BHBA significantly reduces levels of proinflammatory enzymes and proinflammatory cytokines by inhibition of the NF- κ B signaling pathway but not MAPKs pathways, and GPR109A is essential to this function. Overall, these data suggest that BHBA has a potential as neuroprotective drug candidate in neurodegenerative diseases.